Hubungan Antara Pola Asuh Orang Tua dan Lingkungan Sosial dengan Perilaku Merokok pada Remaja di SMAN 2 Depok - Mentari Fajri Romadhona Yahya (2020)
Smokers in Indonesian, mainly in adolescents is continues to increase. There are several of the factors that cause them to smoke among other things parenting and social environment. One of the reason they smoke in order to be accepted among the group that social environment and parents who release their adolescent without good direction. This is certainly a problem because adolescencs are the future generation. The purpose this research is to analyze the parenting and the social environment on adolescent smoking behavior in SMAN 2 Depok. This research is quantitative research with cross sectional design. The population in this research is SMAN 2 Depok students in class X and XI as many as 754. The sampling technique was performed used Stratified Random Sampling and obtained a sample of 262. The result of data analysis used Chi Square test show there is a relationship between parenting on adolescent smoking behavior (p value=0,000) and there is a relationship between social environment on adolescent smoking behavior (p value=0,000). It is recomended for adolescents to increase positive activities such as extracurricular activities in schools, religious activities and others to avoid smoking behavior. The researcher also advises school to monitor adolescents not only from academics but also from adolescent atitudes and behavior